WAKAF UANG DI INDONESIA: TANTANGAN, PELUANG DAN LANGKAH-LANGKAH MENUJU PEMANFAATAN OPTIMAL - Nawawi Nawawi; Mirwan Mirwan; Zainul Anwar; Wawan Juandi (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2024)
Cash endowment has become one of the pivotal instruments in Indonesia's economic and social development. However, after the enactment of Wakaf (Islamic endowment) regulations in 2004, there are still several challenges in the country's optimal utilization of cash endowments. This study aims to conduct an in-depth analysis of the challenges, opportunities, and necessary steps to optimize the utilization of cash endowment in Indonesia after enacting the 2004 Wakaf regulations. The Systematic Literature Review (SLR) method is employed to gather, evaluate, and synthesize various Indonesian cash endowment studies. The analysis reveals that despite challenges such as regulatory ambiguity, lack of public understanding, and administrative hurdles, there are significant opportunities for cash endowment development, including the growth of the Islamic finance sector and increasing government support. Strategic steps such as enhancing public education, regulatory improvements, and collaboration among stakeholders are required to capitalize on these opportunities optimally. This study contributes to a deeper understanding of cash endowment dynamics in Indonesia and guides policymakers, practitioners, and academics in promoting sustainable and inclusive cash endowment development in the future.